COMIC STRIPS AS A HELP IN WRITING SHORT STORY TEXTS - Faiz Amriana; Harjito Harjito; Ika Septiana (Universitas PGRI Semarang, 2023)
The learning achievement of students of class IX MTs N Rembang in learning short story texts is still not optimal. As a student it is not finished. Students who get scores beyond the Minimum Completeness Criteria (KKM) are things that must be fulfilled. The low achievement of the learning outcomes is from learning factors that are less interesting and monotonous, students have difficulty expressing the contents of their thoughts to be conveyed in writing. This research develops learning media with comic strips media. The purpose of writing this thesis is to describe prototypes of short story teaching materials using comic strips media at MTs N Rembang. This research was conducted to use the Research and Development method from Borg and Gall's theory which was adapted as needed. The results of the expert validation showed that the developed comic strips received a score of 96% in the very good category to be tested. After being validated, the teaching media was tested on MTs N 4 and MTs N 3 Rembang students. The trial results showed that many students scored above the KKM even though there were some who had not completed KD in writing short story texts. From the data that has been analyzed, it can be concluded that comic strips media is one of the solutions that can be used in learning short story texts.Keywords : comic strips, instructional media, short story